2014
DOI: 10.1002/tie.21670
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency-Seeking Emerging Market Firms: Resources and Location Choices

Abstract: We study the efficiency‐seeking location choices of Indian software firms. In particular, we investigate the influence of heterogeneity in their resources on their location choices. The resource‐based view posits that firms face difficulties in transferring their resources in dissimilar host‐country environments. Prior research has investigated this phenomenon primarily for market‐seeking motives of multinational firms. With the help of hierarchical linear modeling, we analyze 650 location choices of Indian so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…The costs associated with a liability of foreignness typically outweigh the incremental benefits of early internationalization (Contractor, Kundi, & Hsu, ; Oh & Contractor, ; Wei & Clegg, ); however, our theorizing suggests that coopetition with home‐country governments and global rivals can provide the resources necessary to overcome these costs or at least provide cost‐sharing scenarios. This is in line with recent work showing that specific resources or core competences can help EMNEs overcome the difficulties of dissimilar international contexts (Jain, Kundu, & Newburry, ). Moreover, coopetitive arrangements offer one avenue of exploration beneficial in overcoming information deprivation, a key element of the liability of foreignness (Wei & Clegg, ).…”
Section: Discussionsupporting
confidence: 90%
“…The costs associated with a liability of foreignness typically outweigh the incremental benefits of early internationalization (Contractor, Kundi, & Hsu, ; Oh & Contractor, ; Wei & Clegg, ); however, our theorizing suggests that coopetition with home‐country governments and global rivals can provide the resources necessary to overcome these costs or at least provide cost‐sharing scenarios. This is in line with recent work showing that specific resources or core competences can help EMNEs overcome the difficulties of dissimilar international contexts (Jain, Kundu, & Newburry, ). Moreover, coopetitive arrangements offer one avenue of exploration beneficial in overcoming information deprivation, a key element of the liability of foreignness (Wei & Clegg, ).…”
Section: Discussionsupporting
confidence: 90%
“…Hasan (2002) and Basu and Das (2015) suggested that in medium and short run, use of technology is the most important determinant of corporate profitability and efficiency in the Indian organized manufacturing sector. Some of the other important factors identified by different research studies were size of the firm, age of the firm, ownership structure, number of employees, profitability, prevalence of competition, liberalisation, exports, labour cost, foreign ownership, capitalisation, subsidies, management costs, education of the owners, quality of human capital, , R & D, innovation, existence of crimes and political risk, infrastructure, product diversification and international diversification, use of technology, managerial efficiency, remuneration of the top management and workers, market to book value ratio, financial leverage, early adoption of technology, governance quality, government grants and assistance, rate of taxes, foreign investment and training cost of employees (Baek & Neymotin, 2016;Blomström, 1986;Biener et al, 2016;Castiglione & Infante, 2014;Chapelle & Plane, 2005;Chuang & Lin, 1999;Diaz-Balteiro et al, 2006;Doaei et al, 2015;Firth et al, 2015;Forlani, 2012;Giokas et al, 2015;Hanousek et al ,2015;Ismail & Sulaiman, 2007;Jain et al, 2015;Kumbhakar et al, 1991;O'Toole and Tarp, 2014;Piesse & Thirtle, 2000;Pitt & Lee, 1981;Thatcher & Oliver, 2001;Weill, 1992;Yu et al, 2012;Zhang et al, 2003;Zheng et al, 1998). Amongst all factors, ownership (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Henisz and Macher (2004) revealed that firms' decisions to locate their affiliates are not only influenced by location factors but also by their own capability. Jain, Kundu, and Newburry (2015) stated that the linkage location choice of cross-border mergers and acquisitions of Indian pharmaceutical companies. Das and Banik (2015) investigated the motives of internationalization of Indian multinationals, using firm destination data.…”
Section: Introductionmentioning
confidence: 99%